College geometry a problem-solving approach with applications - Musser, Gary L. (Macmillan College Pub., 1994)
This book exposes readers to many practical applications of geometry, especially those involving measurement. A three- part organization divides topics into Problem Solving, Geometric Shapes, and Measurement; Formal Synthetic Euclidean Geometry; and Alternate Approaches to Plane Geometry.